Effect of Bacteriophages on Viability and Growth of Co-cultivated Weissella and Leuconostoc in Kimchi Fermentation - Kong, Se-jin; Park, Jong-Hyun (Journal of microbiology and biotechnology, 2019)
This study aimed to understand the survival and growth patterns of bacteriophage-sensitive Weissella and Leuconostoc strains involved in kimchi fermentation. Dongchimi kimchi was prepared, and Weissella and Leuconostoc were co-cultivated in the Dongchimi broth. Weissella cibaria KCTC 3807 growth was accompanied by rapid lysis with an increase in the bacteriophage quantity. Leuconostoc citreum KCCM 12030 followed the same pattern. The bacteriophage-insensitive strains W. cibaria KCTC 3499 and Leuconostoc mesenteroides KCCM 11325 survived longer under low pH as their growth was not accompanied by bacteriophages. The bacteriophage lysate of W. cibaria KCTC 3807 accelerated and promoted the growth of Leuconostoc. Overall, our results show that bacteriophages might affect the viability and population dynamics of lactic acid bacteria during kimchi fermentation.